Information System of Product Distribution In CV. Trianom Agrotektur - Ahmad Fikri; Leonardi Paris Hasugian (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2019)
CV. Trianom Agrotektur is a company that runs on coffe industry as a supplier of pristine coffee products without a mixture under Kadatuan Koffie brand, located on Jl. Karawitan No. 48, Bandung. Activities in distributing their coffee products especially to partners, ordering goods made by partners is still through communication media (social media or telephone), then each order data is processed using the Microsoft Office Excel program which will certainly take a long time. In addition, there is no data management for procurement of inventory and returns. The purpose of the research is to build an information system for managing order data from business partners to speed up in making report, build information systems of return from order goods of business partners, and procure inventory on CV. Trianom Agrotektur. As for several methods to meet the needs of building a proposed system, it is data collection methods (primary and secondary), object-oriented system approach methods, and the method of developing the waterfall system. In programming languages, the author uses the PHP programming language in the Laravel framework and MySQL as database management. It is expected that by conducting this research, that is building an information system of supply that can speed up the making of order reports from business partners and their management, and provide a means of managing data procurement and returns.